IMPLEMENTASI DYNAMIC GOVERNANCE PADA PROGRAM PENANGANAN PANDEMI COVID-19 DI DESA SANUR KAJA - Ikhlas, Zaitul; Erawan, I Ketut Putra; jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study seeks to find out how the implementation of policies for handling the Covid-19 pandemic in Sanur Kaja Village. This study uses the Theory of Dynamic Governance issued by Neo & Chen. The author found the findings, namely the normative and proactive pattern of village apparatus performance, so this has implications for actors involved in pandemic handling policies that are oriented to Able People and Agile Process-oriented implementation. Second, indicators of adaptive policies and policy implementation can be seen with the issuance of the Minister of Village Decree No. 8 of 2020 concerning changes to Village Funds as a quick step for handling and preventing pandemics, as well as the "green zone" vaccination policy as an effort to reopen tourism in the Sanur area. This research has answered about the implementation of Dynamic Governance in handling the pandemic in Sanur Kaja Village